The Urgency of the Principle of Balance in Consumer Protection in Land Buying and Selling - Iqbal, Dzaka Imtiyaz (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Land has an important function in human life, therefore the law is tasked with providing legal protection and legal certainty for land buyers. Land that is in dispute often creates problems for land buyers who have minimal information about the status of the existing land. So in reality the practice of buying and selling land often ignores existing consumer protection. Therefore, the aim of writing this article is to discuss the urgency of balancing values in consumer protection when buying and selling land. This writing uses sociological juridical methods. Based on the research conducted, data was found in the form of phe protection for buyers who have made payments in the sale and purchase of problematic land is not yet balanced, this is due to the legal culture of sellers who are often dishonest regarding the status of the land, and the existence of third parties related to the seller who also claim rights to a land contribute to the loss of the buyer. The development of efforts through the judiciary is quite long and expensive. ConsequenceThe lack of guaranteed legal certainty and legal protection for problematic land buyers will ultimately harm the principles of legal objectives according to Islam and at the same time the mandate of Pancasila and the 1945 Constitution of the Republic of Indonesia. This will certainly violate social balance for all Indonesian people. Keywords: Buying; Protection; Selling; Value.